PENERAPAN STRATEGI THINK-TALK-WRITE (TTW) DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS X3 SMA NEGERI 4 TANAH PUTIH - Runanda, Istifariani; Siregar, Syarifah Nur; ', Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve ability of understanding mathematical class X3 SMA Negeri 4 Tanah Putih outcomes through of the implementation of the Think-Talk-Write (TTW) strategy in cooperative learning. This research is a colaborative class action research. This type of research is the classroom action research with two cycle. The subject of this research were the students of class X3 SMA Negeri 4 Tanah Putih that consist of 11 boys and 12 girls. The instruments of data collection in this research were observation sheet and students mathematical understanding of abilty test. Based on the result of the research showed that implementation of learning process on cycle I and II had happened improvement learning process. Based on data analysis ability of understanding mathematical students in classical class X3 SMA Negeri 4 Tanah Putih, obtained an average N-gain ability of understanding mathematical students on the first cycle is 0,40 and second cycle is 0,80. Average N-gain ability of understanding mathematical students in crease in cycle I and II, it show that Average N-gain ability of understanding mathematical students more than 0. It shows ability of understanding mathematical students with implementation of Think-Talk-Write (TTW) strategy in cooperative learning is increased. Based on the result of this research could be concluded that the implementation of Think-Talk-Write (TTW) strategy in cooperative learning can improve the learning process and improve ability of understanding mathematical of class X3 of SMA Negeri 4 Tanah Putih in the second semester academic years 2015/2016.Key Words: Ability of Mathematical Understanding, Think-Talk-Write (TTW)Strategy,Cooperative learning, Clasroom Action Research